019 Correlation of visual field loss with mri findings in patients with pituitary tumours. Issue 6 (24th May 2018) - Lueck, Christian J; Kane, Emily; Ashton, David; Mews, Peter; Reid, Kate; Neely, Andrew J
Abstract : Introduction: The exact mechanism that gives rise to bi-temporal hemianopia in chiasmal compression by pituitary tumours is currently unknown. One theory suggests that, because crossing fibres cross each other and therefore have less contact area, they experience greater stress from compressive forces than those experienced by uncrossed fibres (which have a larger contact area). Finite element modelling has been used has been used to investigate this in silico but the hypothesis needs testing in vivo. This study aimed to determine whether extrinsic chiasmal compression was associated with patterns of visual field loss which supported the 'crossing hypothesis' or not. Methods: Subjects with chiasmal compression secondary to pituitary tumours who also had clear visual field abnormalities were identified from the Canberra Hospital database. Visual fields were analysed to derive 'temporality' and 'bi-temporality' indices. MRI scans were analysed to determine the relative elevations of centre and peripheral portions of the optic chiasm and, in turn, the eccentricity of compression. Temporality indices were plotted against central chiasmal elevation, and both temporal and nasal hemi-field abnormalities were plotted against eccentricity. Results: 122 patients were identified but only 12 were suitable for analysis. Both temporality and bi-temporality indices were significantly correlated with central chiasmal elevation (p=0.004). Hemi-field studies demonstrated patterns of visual loss with increasing eccentricity that were more consistent with the 'crossing hypothesis' though the correlations failed to reach significance. Conclusion: This study provides tentative support for the 'crossing hypothesis'. The information will be used to inform further finite element models of chiasmal compression. A larger, prospective study is warranted.